{ (2x+1)/3 - (x-2y)/5 = 4(2x+y)/15 |*15
{ (x-4y)/3 + (5x-11y)/6 = (3x-1)/4 |*12
{ 5*(2x+1) - 3*(x-2y) = 4(2x+y)
{ 4*(x-4y) + 2(5x -11y) = 3*(3x-1)
{10x +5 - 3x +6y = 8x +4y
{ 4x -16y +10x -22y = 9x -3
{ 7x + 6y + 5 = 8x + 4y
{ 14x - 38y = 9x - 3
{ 7x +6y - 8x -4y = - 5
{ 14x - 38y -9x = -3
{ -x +2y = -5 ⇒ 2y = -5+x ⇒ y = (-5+x)/2 ⇒ y= 1/2 * (x-5) ⇒ y=0.5(x-5)
{ 5x - 38y = - 3
Решение методом подстановки:
5x - 38 * 0.5 (x-5) = -3
5x - 19(x-5) = -3
5x - 19x + 95 = -3
-14х = -3-95
-14х= -98
х= -98/(-14)
х= 7
у= 0,5*(7-5)
у= 0,5*2
у=1
Решение методом алгебраического сложения:
{ -x + 2y = -5 |*19
{ 5x - 38y = -3
{ - 19x + 38y = -95
{ 5x - 38y = -3
- 19x + 38y + 5x - 38y = -95 + (-3)
-14x = -98
x= - 98 /(-14)
x = 7
7 + 2y = - 5
2y = - 5 + 7
2y = 2
y = 2/2
y = 1
ответ: ( 7; 1) .